LIVER FUNCTION TESTS IN SECOND AND THIRD TRIMESTER PRIMIGRAVIDA IN NORMAL PREGNANCY AND PREECLAMPSIA - Taimoor, Alruba; Nazir, Aamir; Raza, Nuzhat; Qureshi, Sadaf Anwar; Ayub, Muhammad; Shirwany, Tanvir Ali Khan (Pakistan Journal of Physiology, 2017)
Background: Preeclampsia is a common obstetrical problem affecting 5–10% of pregnant females. The objective of this study was to determine and compare liver function tests in primigravidas in second and third trimesters of normal pregnancy and preeclampsia. Methods: A cross-sectional comparative study was conducted that included 100 subjects aged 15–40 years with normal pregnancy, and preeclamptic primigravidas of second and third trimester. Their liver function tests were carried out and compared among the study groups. Results: The mean age of the subjects was 25.92±5.56 years, mean systolic BP was 136.3±24.623 mmHg, mean diastolic blood pressure was 87.8±15.736 mmHg. There were statistically significant differences in AST, ALT, ALP, and serum albumin among cases and controls of both 2nd and 3rd trimester (p<0.05). However, serum total bilirubin among preeclamptics of 2nd and 3rd trimesters, and also between controls and preeclamptics of 3rd trimester was significantly increased (p<0.05). Serum AST and ALT were significantly decreased among controls of 3rd trimesters compared to 2nd trimester while ALP was significantly increased in 3rd trimester controls compared to 2nd trimester controls. Serum albumin was significantly decreased in both 2nd and 3rd trimester preeclamptics compared to controls. Conclusion: Serum AST, ALP, and bilirubin was significantly increased in 3rd trimester preeclamptics compared to 2nd trimester preeclamptics. Keywords: Preeclampsia, liver function tests, primarygravidas Pak J Physiol 2017;13(2):25–8